A design tool for a parabolic trough collector system for industrial process heat based on dynamic simulation - Ktistis, Panayiotis K.; Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2022)
The industrial sector is one of the biggest oil consumers in Cyprus, corresponding to 20% of the fuel consumption. A parabolic trough collector (PTC) system seems the best option to produce clean thermal energy at higher temperatures than those that can be achieved from the already widely used flat plate collectors on the island. This paper presents a simulation model built to investigate the performance of the first industrial PTC system in Cyprus, installed at the Cyprus biggest soft drinks factory. The simulation model is built in TRNSYS and is validated using data from the real PTC system installed at the factory. The results show a very good fitting between the operating parameters and the power output of the Solar Field (SF), Concrete Thermal Storage System (CTES), and the Steam Generator (SG). The average percentage relative error of the system's contribution to the process is less than 6.32% for the daily steam production and during a week did not exceed 6.45%. The novelty of this study is the development of a design tool that can be used by potential interested industries to identify the suitable system that fits their needs. All data are provided in the form of graphs and allow anyone to use as input data the thermal energy demand and required steam temperature of the industry to retrieve information about the size of a suitable system which satisfies these requirements depending on each case. The payback period for all cases examined varies from 2 to 6 years, depending on the size of the system.
Keywords: Concentrated solar power; Concrete storage; Industrial process heat; Parabolic trough collector; Steam production; Thermal energy storage